Analisis Isi Iklan Televisi di Indonesia - Ali, Moondore Madalina (Humaniora, 2014)
There are no television channels especially for children in Indonesia. Children’s programmes usually air early in the morning or in the afternoon. Most children watch television during Saturday and Sunday where most of them do not have to go to school. Children could watch any programmes airing during those times. There were not many content analysis researches looking at advertiments aired in television before in Indonesia. Therefore, this study looked at advertisements shown on Saturday and Sunday by using quantitative method. Quantitative method used was content analysis. Four private channels were chosen with a total 120 hours of television program recorded on Saturday and Sunday. This study showed that 37 out of 120 hours of television were advertisement with 6898 advertisements (promotion and products). Children in Indonesia were exposed to many advertisements on television on Saturday and Sunday.